Molecular structure of purinergic P2X receptors and their expression in the hypothalamus and pituitary - Zemková, Hana; Balík, Aleš; Jindřichová, Marie; Vávra, Vojtěch (Physiological research, 2008)
Purinergic P2X receptors represent a novel structural type of ligand-gated ion channels activated by extracellular ATP. So far, seven P2X receptor subunits have been found in excitable as well as non-excitable tissues. Little is known about their structure, mechanism of channel opening, localization, and role in the central nervous system. The aim of this work is to summarize recent investigations and describe our contribution to elucidating the structure of the ATP binding site and transmembrane domains of the P2X receptor, we also discuss the expression and physiological roles played by the ATP and P2X receptors in the anterior pituitary and hypothalamus.
Keywords: terciární struktura proteinů; Animals; ivermektin; neurony; neuroglie; Protein Structure, Quaternary; hypofýza; Humans; Ivermectin; Neuroglia; hypothalamus; Protein Binding; vazba proteinů; sekundární struktura proteinů; adenosintrifosfát; Pituitary Gland; Adenosine Triphosphate; Neurons; Models, Molecular; lidé; Receptors, Purinergic P2; zvířata; Gonadotrophs; Hypothalamus; molekulární modely; kvarterní struktura proteinů; Protein Structure, Tertiary; Protein Structure, Secondary; gonadotropní buňky; purinergní receptory P2